2016
DOI: 10.1155/2016/8032528
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Trends in Hypnotics Consumption in the Largest Health Care System in Israel

Abstract: Objectives. To quantify and characterize hypnotics consumption habits among adult patients insured by Clalit Health Services (CHS), the largest health care provider in Israel, in 2000 and 2010. Methods. A retrospective analysis of CHS computerized pharmacy records. Data were collected for all patients over the age of 18 years who were prescribed hypnotics in 2000 and in 2010. Results. Sleep medications were consumed by 8.7% of the adult CHS population in 2000 and by 9.6% in 2010. About one-quarter of consumers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Similarly, we have previously reported that the Arab population is behind the Jewish one in diagnosing and treating obstructive sleep apnea [28]. We also showed that the Arab population consumes signi cantly fewer sleep medications than the Jewish population [29]. This can be explained by poverty, less health knowledge, and ethnicitybased factors, as discussed below.…”
Section: Medication Usesupporting
confidence: 74%
“…Similarly, we have previously reported that the Arab population is behind the Jewish one in diagnosing and treating obstructive sleep apnea [28]. We also showed that the Arab population consumes signi cantly fewer sleep medications than the Jewish population [29]. This can be explained by poverty, less health knowledge, and ethnicitybased factors, as discussed below.…”
Section: Medication Usesupporting
confidence: 74%
“…This is higher than the prevalence in the general population, for instance in Canada (5.5%), 33 Norway (7.9%) 34 or Israel (8.7%). 35 When asked to specify, 87.3% of our population answered benzodiazepines as the medicine of choice, contrasting with 67.1% in Norway. 34 According to the Portuguese Directorate-General of Health, 36 Portugal is the EU country with the highest consumption of this pharmacological class per inhabitant.…”
Section: Discussionmentioning
confidence: 91%
“…Our results and those of another recent study suggest that the use of benzodiazepine/BDZRAs is substantially higher in Israel than in most other Western countries. 22 In the United Overall rate of benzodiazepine/BDZRA use among older adults in 2014 was 32%, and overall rate of heavy use (6 or more dispensings) was 19% *Reference group is patients without each of these conditions or medications…”
Section: Discussionmentioning
confidence: 99%